Effect of different sources of blood feeding on Aedes aegypti (Diptera: Culicidae) under insectary conditions - González-Fernández, Mariana Irina; Vázquez Anzúrez, Miriam Juana; Sesma Medrano, Eduardo; Falcón Lezama, Jorge Abelardo; González Acosta, Cassandra; Correa Morales, Fabián (Horizonte Sanitario, 2019)
Objetive: To evaluate the effect of three sources of blood feeding: New Zealand rabbit, Egyptian rat and human, on the number of eggs laid and percentage of Aedes aegypti larvae hatching under insectary conditions.Materials and methods: To evaluate the effect of three sources of blood feeding: New Zealand rabbit, Egyptian rat and human, on the number of eggs laid and percentage of Aedes aegypti larvae hatching under insectary conditions.Results: A statistical significant difference was observed in the average of eggs placed between the three pools of Aedes aegypti females fed different blood sources: rat blood, 671.25 eggs; human blood, 268.14 eggs and rabbit blood, 209.08 eggs (X2= 10.666, P